2006
DOI: 10.1158/1078-0432.ccr-05-1603
|View full text |Cite
|
Sign up to set email alerts
|

The role of interleukin 1 in growth and metastasis of human cancer xenografts.

Abstract: Background: Interleukin 1 (IL-1) is a pluripotent cytokine that promotes angiogenesis, tumor growth, and metastasis in experimental models; its presence in some human cancers is associated with aggressive tumor biology. The purpose of these studies was to characterize the role of IL-1in human cancers and determine if inhibition of IL-1via its receptor antagonist, IL-1Ra, alters tumor growth and metastatic potential. Methods: IL-1mRNA or protein levels were determined in clinical tumor samples, cancer cell line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
197
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 259 publications
(215 citation statements)
references
References 37 publications
13
197
0
3
Order By: Relevance
“…This overexpression is abrogated by additional presupplementation of IL‐1RA. Moreover, Elaraj et al 81. have demonstrated that IL‐1RA inhibits the growth of colonic adenocarcinoma cell line xenografts in nude mice.…”
Section: Resultsmentioning
confidence: 99%
“…This overexpression is abrogated by additional presupplementation of IL‐1RA. Moreover, Elaraj et al 81. have demonstrated that IL‐1RA inhibits the growth of colonic adenocarcinoma cell line xenografts in nude mice.…”
Section: Resultsmentioning
confidence: 99%
“…DA/3 mammary cancer cells fail to grow tumors in the foot pad of IL-1␣ KO mice, whereas progressive tumor growth is observed in wildtype mice. In support of these findings, the expression of IL-1 is significantly increased in a variety of malignant lesions and particularly in metastatic human tumor specimens, including nonsmall cell lung cancer, colorectal carcinoma, and melanoma (7,8). Furthermore, antagonism of IL-1R using IL-1R antagonist results in significant inhibition of angiogenesis and growth of xenografted human tumors that produce IL-1.…”
mentioning
confidence: 85%
“…We hypothesized that IL-1β could alter KLF5 expression in pancreatic cancer cells, as this cytokine is relevant for pancreatic cancer progression due to its complex implication in cancer growth (22) and angiogenesis (23)(24)(25). IL-1β has been reported to activate multiple signaling pathways, thus promoting cell proliferation, up-regulation of vascular endothelial growth factor, cell survival, and metastasis (16,23,26).…”
Section: Effect Of Il-1β On Klf5 Expression In Pancreatic Cancer Cellsmentioning
confidence: 99%